The syntax of wh-movement in modern standard Arabic - سهير فرج (Faculty of Languages Journal-Tripoli-Libya, 2021)
Three types of syntactic movement have been studied; head movement, argument movement (A- movement), and non-argument movement (Wh-movement or A' movement). This paper deals with the formation of wh- questions in Modern Standard Arabic within Government Binding theory (Chomsky 1986) and Optimality Theory (Prince, A and Smolensky 1993).